1991
DOI: 10.1029/91jb01618
|View full text |Cite
|
Sign up to set email alerts
|

Late Cretaceous paleomagnetism of the Tucson Mountains: Implications for vertical axis rotations in south central Arizona

Abstract: The Tucson Mountains of southern Arizona are the site of an Upper Cretaceous caldera from which the rhyolitic Cat Mountain Tuff was erupted at about 72 Ma. Two magnetic units within the Cat Mountain Tuff are distinguished by paleomagnetic data in both the northern and southern Tucson Mountains. The resurgent Amole pluton (≃72 Ma) in the northern Tucson Mountains was emplaced soon after eruption of the Cat Mountain Tuff but cooled and was magnetized after northeastward tilting (50°–85°) of the adjacent caldera‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…In a nutshell, tuff erupted from the Silver Bell caldera (tuff of Confidence Peak) is present as megablocks within the younger Tucson Mountains caldera, and the welded tuff member of the Mount Lord Volcanics that caps the Silver Bell Mountains is now interpreted as outflow Cat Mountain Tuff from the Tucson Mountain caldera. These correlations are confirmed by distinctions in petrography, minorelement compositions, and paleomagnetic pole positions (table I; Hagstrom and Sawyer, 1989;Hagstrom and Lipman, 1991).…”
Section: Central Part Of Caldera Fill At Gates Passsupporting
confidence: 48%
See 2 more Smart Citations
“…In a nutshell, tuff erupted from the Silver Bell caldera (tuff of Confidence Peak) is present as megablocks within the younger Tucson Mountains caldera, and the welded tuff member of the Mount Lord Volcanics that caps the Silver Bell Mountains is now interpreted as outflow Cat Mountain Tuff from the Tucson Mountain caldera. These correlations are confirmed by distinctions in petrography, minorelement compositions, and paleomagnetic pole positions (table I; Hagstrom and Sawyer, 1989;Hagstrom and Lipman, 1991).…”
Section: Central Part Of Caldera Fill At Gates Passsupporting
confidence: 48%
“…(Sawyer, 1987). The capping tuffs of the Silver Bell Mountains have at times been designated the Mount Lord Tuff (Ignimbrite), but correlation with the Cat Mountain Tuff (which has precedence as a name) is now frrmly based on stratigraphic position with respect to the tuff of Confidence Peak (erupted from the Silver Bell caldera), petrographic and chemical distinctions, and distinctive paleomagnetic pole positions (Hagstrom and Sawyer, 1989;Hagstrom and Lipman, 1991).…”
Section: Notched Roadcut Outcrops Are Weakly Welded Catmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, each one of those poles carries associated irresolvable uncertainties: igneous rock paleopoles including the Moat Volcanics possess a paleohorizontal uncertainty, whereas the Corral Canyon sites lie within a tectonic block which subsequently has been detached from the North American craton. Studies of other Basin and Range blocks in the geographic area have demonstrated that these blocks have been rotated relative to cratonic North America [e.g., Hagstrum and Lipman , 1991]. Thus without corroborating evidence, the Corral Canyon pole cannot be considered a reliable reflection of NA Jurassic APW.…”
Section: Resultsmentioning
confidence: 99%
“…Locally, the volcanic rocks include coarse and (or) exotic-breccia deposits. To the west, the rhyolite tuffs are known as the upper member of the Salero Formation (Drewes, 1971c) or the Cat Mountain Tuff (Cooper, 1973;Drewes, 198la;Hagstrum and Lipman, 1991).…”
mentioning
confidence: 99%